Effects of aloe vera extract in drinking water on broiler performance - Islam, Md Mirajul; Rahman, Md Mamunur; Sultana, Salma; Hassan, Md Zakir; Miah, Abdul Gaffar; Hamid, Md Abdul (Asian Journal of Medical and Biological Research, 2017)
This experiment was conducted to evaluate the effects of dietary supplementation of aloe vera extract (w/v) on growth performance of broiler. The present study explored the potentials of medicinal plants Aloe barbedensis mixture in broiler performance. For this purpose, 120 day old chicks were randomly assigned into five treatment groups, namely T0, T1, T2, T3 and T4. Each treatment group contained 24 chicks. The chicks were purchased from a local chick hatchery named Nourish Poultry & Hatchery Ltd. Birds were brooded up to 10 days and then reared in separate flock for 35 days in an open sided house. Each treatment group was further replicated into three sub-groups and each contained eight birds. Experimental birds in T1, T2, T3 and T4 were provided with aloe vera extract (w/v) @ 05, 10, 15 and 20 ml per liter of drinking water while T0 was maintained as control group. Relevant data were recorded throughout the experimental period and subjected to statistical analysis. The data on growth parameters (body weight gain, feed consumption, feed efficiency, water intake) and feed cost and gross return per broiler were evaluated. The results of the study revealed that the aloe vera supplemented groups showed higher live weight gain than untreated group. Aloe vera supplemented groups showed more live weight gain in the terminal stages of the experiment. Aloe vera (w/v) extract supplemented groups performed the best feed efficiency. The live weight gain and feed efficiency were significantly (P<0.05) better in the broilers provided water containing 15 ml/L aloe vera aqueous extract. Water intake, feed intake and abdominal fat deposition of broilers given aloe extract in drinking water were not different among each other. So, 15 ml/L aloe vera aqueous extract may be given to the broilers drinking water. Asian J. Med. Biol. Res. March 2017, 3(1): 120-126